Land Use Change and Its Impact on Soil Quality Based on GIS and Soil Quality Index (SQI) in the Manten Sub-Watershed, Malang, Indonesia - Suhari, Reza Hasan; Maroeto, Maroeto; Priyadarshini, Rossyda (Agro Bali : Agricultural Journal, 2025)
This study aims to analyze land use change and its impact on soil quality in the Catchment Area of the Manten Sub-watershed, Malang Regency. Land use changes were assessed using satellite imagery data from 1998, 2008, 2018, and 2024, while soil physical and chemical properties were measured to develop the Soil Quality Index (SQI). The SQI was computed using the Minimum Data Set (MDS) approach based on principal component analysis, and each indicator was scored and integrated using a weighted additive formula. The results show a significant increase in built-up areas by 12% and a decrease in plantation land due to land conversion. These changes were driven by population growth and urbanization. The highest SQI value was recorded in plantation areas (0.70), while the lowest was found in dryland agriculture (0.58). The decline in soil quality was mainly caused by low organic matter content and unsustainable land management practices. This study highlights the importance of land use planning based on soil potential to support environmental sustainability.